CSF neurofilament concentration reflects disease severity in frontotemporal degeneration - Scherling, Carole S. (2014)
OBJECTIVE: Cerebrospinal fluid (CSF) neurofilament light chain (NfL) concentration is elevated in neurological disorders including frontotemporal degeneration (FTD). We investigated the clinical correlates of elevated CSF NfL levels in FTD. METHODS: CSF NfL, amyloid-β(42) (Aβ42), tau and phosphorylated tau (ptau) concentrations were compared in 47 normal controls (NC), 8 asymptomatic gene carriers (NC2) of FTD-causing mutations, 79 FTD (45 behavioral variant frontotemporal dementia [bvFTD], 18 progressive nonfluent aphasia [PNFA], 16 semantic dementia [SD]), 22 progressive supranuclear palsy, 50 Alzheimer’s disease, 6 Parkinson’s disease and 17 corticobasal syndrome patients. Correlations between CSF analyte levels were performed with neuropsychological measures and the Clinical Dementia Rating scale sum of boxes (CDRsb). Voxel-based morphometry of structural MR images determined the relationship between brain volume and CSF NfL. RESULTS: Mean CSF NfL concentrations were higher in bvFTD, SD and PNFA than other groups. NfL in NC2 was similar to NC. CSF NfL, but not other CSF measures, correlated with CDRsb and neuropsychological measures in FTD, and not in other diagnostic groups. Analyses in two independent FTD cohorts and a group of autopsy verified or biomarker enriched cases confirmed the larger group analysis. In FTD, gray and white matter volume negatively correlated with CSF NfL concentration, such that individuals with highest NfL levels exhibited the most atrophy. INTERPRETATION: CSF NfL is elevated in symptomatic FTD and correlates with disease severity. This measurement may be a useful surrogate endpoint of disease severity in FTD clinical trials. Longitudinal studies of CSF NfL in FTD are warranted.